Cultivation of Synechococcus HS-9 in a novel rectangular bubble column photobioreactor with horizontal baffle. (October 2021) - Rahman, Arif; Putra, Juno Dwi; Prihantini, Nining Betawati; Mahlia, T.M.I.; Aziz, M.; Deendarlianto; Nasruddin, N.
Abstract: As a source for third-generation biofuel, microalgae can assist island countries to overcome their energy crisis. In this study, a novel photobioreactor having three segments is designed and Synechococcus HS-9 growth in the photobioreactors with and without a baffle is compared. The aims of this study are to investigate how the baffle influences bubble size, distribution, and velocity, to explain the bubble coalescence phenomena, and verify the effect of the baffle on Synechococcus HS-9 growth. The results showed that bubble size distribution in the photobioreactors paralleled the increasing air flow rate. At a flow rate of 1.0 L/min, most bubbles had a diameter of 200–400 μm; however, at 2.5 L/min, the typical size was 1400–2000 μm. Bubble velocity was observed through imaging techniques. The intake air flow rate of 1 LPM has a mass transfer coefficient value of 0.00075 m/s for the photobioreactor without the baffle and 0.00089 m/s for the baffle-bearing photobioreactor. The Sauter mean diameters at three different heights (A, B and C section) in the photobioreactors were 675 μm, 1001 μm, and 1125 μm. Synechococcus HS-9 growth was 2.17 times higher in the baffle-bearing photobioreactor than that in the photobioreactor without the baffle. Graphical abstract: Image 1 Highlights: Cultivation of Synechococcus HS-9 in a novel rectangular bubble column photobioreactor Bubble size distribution in a photobioreactor using a baffle and without a baffle Bubble coalescence phenomena in a photobioreactor Synechococcus HS-9 growth in a photobioreactor